History Dependence, Cohort Attachment, and Job Referrals in Networks of Close Relationships - Ayal Chen-Zion; James E. Rauch (Center for Economic Studies and ifo Institute (CESifo), 2019)
We model network formation in a firm. Agents learn about the quality of their working relationships with each other. Their good relationships become their networks. Accumulating relationships becomes increasingly costly, however. Over time agents become less open to forming relationships with others unknown to them, leading their networks to be front-loaded with agents they met near the beginning of their careers. The interaction of this dynamic with turnover yields predictions about the time pattern of history dependence in an agent's network as a function of his tenure. Mutual openness of newly arrived agents in a firm also leads to the cross-section prediction of "cohort attachment," a tendency for members of an agent's hiring cohort to be disproportionately represented in his network. When members of a network formed within a firm are subsequently split across many firms, the desire to renew their successful working relationships can lead to job referrals. Former co-workers who provide referrals will be drawn disproportionately from the referred workers' hiring cohorts at their previous employers.
Keywords: D85; J63; J64; 330; networks; history dependence; job referrals